The Binding Force of A Fiducia Deed In Which There is An Element of Dwaling (Defect of Will) - Noor, Aslan; Dibrata, Shintadewi; Purnama, Selly; Meliani, Indri (Journal of Law, Politic and Humanities, 2024)
Dwaling is a defect of will that can lead to the invalidation of an agreement if one party gives consent based on misinformation. This study uses the juridical analysis method to assess 50 fiduciary deed cases, of which 20% contain dwaling elements. The results show that dwaling often occurs due to the lack of in-depth verification by the notary and unclear communication between the relevant parties. As a result, fiduciary deeds containing dwaling are often declared null and void, causing financial losses for creditors and legal risks for debtors. This research highlights the importance of due diligence, transparency, and strict supervision of the notary profession to prevent dwaling and ensure legal certainty in fiduciary agreements. Recommendations include strengthening regulations, improving understanding of related parties, and stricter enforcement of notary ethical standards. This research aims to provide greater insight into the importance of integrity in fiduciary deed making and the steps needed to mitigate the risk of dwaling.